Airborne observations of the microphysical structure of two contrasting cirrus clouds. Issue 22 (16th November 2016) - O'Shea, S. J.; Choularton, T. W.; Lloyd, G.; Crosier, J.; Bower, K. N.; Gallagher, M.; Abel, S. J.; Cotton, R. J.; Brown, P. R. A.; Fugal, J. P.; Schlenczek, O.; Borrmann, S.; et al.
Abstract: We present detailed airborne in situ measurements of cloud microphysics in two midlatitude cirrus clouds, collected as part of the Cirrus Coupled Cloud‐Radiation Experiment. A new habit recognition algorithm for sorting cloud particle images using a neural network is introduced. Both flights observed clouds that were related to frontal systems, but one was actively developing while the other dissipated as it was sampled. The two clouds showed distinct differences in particle number, habit, and size. However, a number of common features were observed in the 2‐D stereo data set, including a distinct bimodal size distribution within the higher‐temperature regions of the clouds. This may result from a combination of local heterogeneous nucleation and large particles sedimenting from aloft. Both clouds had small ice crystals (<100 µm) present at all levels However, this small ice mode is not present in observations from a holographic probe. This raises the possibility that the small ice observed by optical array probes may at least be in part an instrument artifact due to the counting of out‐of‐focus large particles as small ice. The concentrations of ice crystals were a factor ~10 higher in the actively growing cloud with the stronger updrafts, with a mean concentration of 261 L −1 compared to 29 L −1 in the decaying case. Particles larger than 700 µm were largely absent from the decaying cirrus case. A comparison with ice‐nucleating particle parameterizations suggests that for the developing case the ice concentrations at the lowest temperatures are best explained by homogenous nucleation. Key Points: Distinct differences in ice crystal number, size, and habit observed in decaying and developing midlatitude cirrus clouds Bimodal size distributions are observed by optical array probes, but a holographic probe suggests that these may be instrument artifacts Evidence for both heterogeneous and homogeneous ice nucleation is observed in the clouds